RANCANG BANGUN SENSOR KAPASITIF UNTUK LEVEL AIR - Zahrotin, Eli; Endarko, Endarko (BERKALA FISIKA, 2014)
Capacitive sensor for measuring water level has successfully been fabricated and characterized. Capacitive water level sensor has been fabricated using coaxial cylinder with an inner and outer radius at 0,955 and 1,435 cm, respectively. The cylinders have a length of 82 cm. The study was used water and air as dielectrics for filling in the space of two cylinders. The design of sensor based on the principle of cylindrical capacitor with two dielectrics. Measurements of water level repeated three times to ensure an accuracy of data. The ruler was used as calibrator for measurement of water level. The result showed that the capacitive water level sensor can be used to measure water level with the maximum of standar deviation around 1,40, when the system was used to measure increased water levet at 50 cm and standar deviation minimum at 0,01 occured when it was used to measure decreased water level at 0 cm. Range of measurement was 0,16 -78,99 cm with an average error value when measurements of increased and decreased water level was 2.30 and 1.75%, respectively. Keywords: water level, capacitive, coaxial cylinder.